Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1158/1078-0432.ccr-07-4592
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Crossover Pharmacokinetic Study of Solvent-Based Paclitaxel and nab-Paclitaxel

Abstract: Purpose: Abraxane (ABI-007) is a 130-nm albumin-bound (nab) particle formulation of paclitaxel, devoid of any additional excipients. We hypothesized that this change in formulation alters the systemic disposition of paclitaxel compared with conventional solvent-based formulations (sb-paclitaxel; Taxol), and leads to improved tolerability of the drug. Patients and Methods: Patients with malignant solid tumors were randomized to receive the recommended single-agent dose of nab-paclitaxel (260 mg/m 2 as a 30-minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
148
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 17 publications
(15 reference statements)
6
148
1
2
Order By: Relevance
“…Additional studies involving other tumor models and in vivo mechanism-related studies have confirmed the high accumulation characteristics of Nab-PTX (24,25,29,32). It is generally considered that the free or unbound form of the drug is the active fraction, since drug bound to proteins or other macromolecules may be unable to cross cell membranes (30).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additional studies involving other tumor models and in vivo mechanism-related studies have confirmed the high accumulation characteristics of Nab-PTX (24,25,29,32). It is generally considered that the free or unbound form of the drug is the active fraction, since drug bound to proteins or other macromolecules may be unable to cross cell membranes (30).…”
Section: Discussionmentioning
confidence: 97%
“…The advantage of Nab-PTX is its water solubility, achieved without the use of Cre-EL and ethanol. Indeed, Gardner et al (32) reported that the formulation of Nab-PTX allowed a much higher fraction of unbound paclitaxel than that of Sb-PTX, and that the maximal concentration of unbound paclitaxel was ~10-fold higher for Nab-PTX in their pharmacokinetic study.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel is entrapped by the formation of plasma Cremophor EL micelles, which can cause reduced drug clearance, nonlinear pharmacokinetics, and free drug fraction 14 . The dose-dependent antitumour response from paclitaxel can be decreased as a result 15 . It is this drug a Schedule of nab-paclitaxel was not a significant predictor of overall survival, nor was the interaction between nab-paclitaxel schedule and achievement of clinical benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several preclinical studies reported an approximately 10-fold endothelial binding of nab-paclitaxel, and 4-fold higher levels of transocytosis through endothelial cells in contrast to the solvent based paclitaxel allowing for a dose dependent antitumor activity [43,44].…”
Section: Molecular Mechanismsmentioning
confidence: 99%